MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DALAM MATERI PERISTIWA LAHIRNYA PANCASILA MENGGUNAKAN MEDIA POP UP BOOK - Aris Anwar, Yeni Sulaeman, Omah Mukarromah (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2024)
This article focuses on improving student learning outcomes in Pancasila education subjects regarding the birth of Pancasila using pop up book media in class V at SDN Sukacai 3. This research stage was carried out in 3 cycles, starting with a pre-cycle first. The results of the research showed that in the pre-cycle they only got an average score of 52.84 with a completeness presentation of 44% and in the first cycle there was a decrease to 50.68 with a completeness percentage of 36%, but in the second cycle there was an increase reaching an average score of 60 .08 with a completion percentage of 68%, and in cycle III the students' average score increased to 78.2 with a percentage of 88%. The results of classroom action research concluded that pop up book media could improve student learning outcomes regarding the event of the birth of Pancasila. The role of pop up book media can be an effective alternative in learning Pancasila education regarding the event of the birth of Pancasila for teachers.